A Behcet’s Disease Patient with Right Ventricular Thrombus, Pulmonary Artery Aneurysms, and Deep Vein Thrombosis Complicating Recurrent Pulmonary Thromboembolism - Selvi Aşker; Müntecep Aşker; Özgür Gürsu; Rıdvan Mercan; Özgür Bülent Timuçin (Case Reports in Pulmonology)
Intracardiac thrombus, pulmonary artery aneurysms, deep vein thrombosis, and pulmonary thromboembolism are rarely seen symptoms of Behcet’s disease. A 20-year-old female patient was admitted for complaints of cough, fever, palpitations, and chest pain. On the dynamic thorax computed tomograms (CT) obtained because of significantly enlarged hilar structures seen on chest radiograms, aneurysmal dilatation of the pulmonary artery segments bilaterally, chronic thrombus with collapse, and consolidation substances compatible with pulmonary embolism involving both lower lobes have been observed. It is learned that, four years ago, the patient had been diagnosed with Behcet’s disease and received colchicine treatment but not regularly. The patient was hospitalized. On the transthoracic echocardiogram, a thrombosis with a dimension of 4.2 × 1.6 cm was recognized in the right ventricle. On abdomen CT, aneurysmal iliac veins and deep vein thrombus on Doppler ultrasonograms were diagnosed. At the controls after three months of immunosuppressive and anticoagulant therapies, some clinical and radiological improvements were recognized. The patient suspended the treatment for a month and the thrombus recurred. We present our case in order to show the effectiveness of immunosuppressive and anticoagulant therapies and rarely seen pulmonary thromboembolism in recurrent Behcet’s disease.